Proceedings of the Eleventh Workshop on Visualization for Cyber Security 2014
DOI: 10.1145/2671491.2671492
|View full text |Cite
|
Sign up to set email alerts
|

Visualization evaluation for cyber security

Abstract: The Visualization for Cyber Security research community (VizSec) addresses longstanding challenges in cyber security by adapting and evaluating information visualization techniques with application to the cyber security domain. This research effort has created many tools and techniques that could be applied to improve cyber security, yet the community has not yet established unified standards for evaluating these approaches to predict their operational validity. In this paper, we survey and categorize the eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 37 publications
1
32
0
1
Order By: Relevance
“…Staheli et al [20] presented a survey, in 2014, of 130 VizSec (IEEE Symposium on Visualization for Cyber Security) papers which showed that little research had been conducted in determining the effectiveness of cyber-security visualization. It also showed that 46% of these papers did not have any user-involvement in the evaluation phase.…”
Section: Background Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Staheli et al [20] presented a survey, in 2014, of 130 VizSec (IEEE Symposium on Visualization for Cyber Security) papers which showed that little research had been conducted in determining the effectiveness of cyber-security visualization. It also showed that 46% of these papers did not have any user-involvement in the evaluation phase.…”
Section: Background Literaturementioning
confidence: 99%
“…Additionally, the evaluation techniques used to evaluate most tools were not effective in evaluating the visualizations that were produced based on the performed task nor were the evaluation techniques standardized. The lack of a common framework for standardized evaluation methods [20] has been concluded many times, but there is no research supporting the development of a framework to evaluate the effectiveness of cybersecurity visualization tools based on user requirements. Thus, creating a need for guidelines to standardize evaluation techniques and evaluate for effectiveness of performed task.…”
Section: Background Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…The visualisation of complex knowledge and information structures helps learners to better perceive complex concepts. Visual methods such as AMTs have considerable value in aiding cyber-attack perception [10,11]. Fithen et al, [12] outline the benefits of attack visualisation by arguing that AMTs enable non-experts to better understand and interpret attack models with little reference to logical models.…”
Section: Introductionmentioning
confidence: 99%